Glycaemic Response to a Nut-Enriched Diet in Asian Chinese Adults with Normal or High Glycaemia: The Tū Ora RCT - Sequeira-Bisson IR; Lu LW; Silvestre MP; Plank LD; Middleditch N; Acevedo-Fani A; Parry-Strong A; Hollingsworth KG; Tups A; Miles-Chan JL; Krebs JD; Foster M; et al. (MDPI (Basel, Switzerland), 2024)
Nut-based products are a good source of high-quality plant protein in addition to mono- and polyunsaturated fatty acids, and may aid low-glycaemic dietary strategies important for the prevention of type 2 diabetes (T2D). In particular, they may be advantageous in populations susceptible to dysglycaemia, such as Asian Chinese. The present study aimed to compare effects of a higher-protein nut bar (HP-NB, also higher in total fibre and unsaturated fats, comprising mixed almonds and peanuts) vs. an isoenergetic higher-carbohydrate cereal bar (HC-CB) within the diet of 101 Chinese adults with overweight and normo- or hyperglycaemia. Ectopic pancreas and liver fat were characterised using magnetic resonance imaging and spectroscopy (MRI/S) as a secondary outcome. Participants were randomized to receive HP-NB or HC-CB daily as a 1 MJ light meal or snack replacement, in addition to healthy eating advice. Anthropometry and clinical indicators of T2D risk were assessed fasted and during an oral glucose tolerance test (OGTT), pre- and post-intervention. No significant difference was observed between diet groups for body weight, body mass index, waist or hip circumference, blood pressure, glucoregulatory markers, lipid profile or inflammatory markers over 12 weeks (all, p > 0.05). No difference was observed between glycaemic subgroups or those with normal versus high ectopic organ fat. Although HP-NB can attenuate postprandial glycaemia following a meal, no effects were observed for either fasting or glucose-mediated outcomes following longer-term inclusion in the habitual diet of Chinese adults with overweight, including at-risk subgroups.
Keywords: MRI; almonds; blood glucose; ectopic organ fat; overweight; peanuts; prediabetes; Humans; Male; Female; Nuts; Blood Glucose; Middle Aged; Adult; Diabetes Mellitus, Type 2; Hyperglycemia; China; Asian People; Diet; Glucose Tolerance Test; Overweight; Prunus dulcis; Arachis; East Asian People